Analysis of the Application of SAK EMKM (Accounting Standards for Micro, Small and Medium Entities) in the Preparation of Simple Financial Reports in TUNGKU IBU MSMEs - Ekasari, Ratna; Aisyah, Siti (IQTISHADequity jurnal MANAJEMEN, 2024)
This research methodology uses qualitative descriptive data using primary and secondary data taken from Tungku Ibu, an MSME company. Data collection was carried out through observation, interviews and documentation.The results of this study show that: 1) the financial recording system is implemented manually and is still very simple, 2) Tungku Ibu UMKM does not carry out financial reporting in accordance with SAK EMKM, 3) The inhibiting factor is the failure to implement SAK EMKM UMKM Tungku Ibu UMKM business due to internal factors in the form of ignorance , lack of discipline and manpower. Meanwhile, external factors are the parties who have an interest in the transaction.